Pedagogy and construction of independent knowledge (2018)
A critical reflection on the pedagogical foundation for the training of autonomous, ethical, and political researchers is made based on the contextual and social reality in Latin America. To this end, it is taken as a point of departure the following question: from a perspective of politics and social ethics, what could be the pedagogical foundation for the training of an autonomous researcher? A literature review was conducted and critical points as well as alternative proposals were stablished as possible pedagogical foundations for the training of researchers in social sciences and education. It is important to highlight how the alternative pedagogical proposals in Latin America have provided critical elements from praxis to education. These elements are strongly linked to the political field because there is a permanent utopia focusing on transformation and a shift towards autonomy development and independence.